The Concept of ‘Villain Characters’ Based on Readers’ Point of View: A Cognitive Linguistics Study - Adnania Nugra Heni (English Letters Department, Faculty of Letters, Universitas Sanata Dharma, 2026)
This study investigates how villain characters are conceptualized by readers through metaphorical expressions found in online reading platforms. Employing a descriptive qualitative design within a cognitive linguistics framework, the data consist of reader comments containing metaphorical language collected from Webtoon and Kakaopage. A total of 60 comments were purposively selected from three popular stories, focusing exclusively on sentences that contain metaphorical expressions referring to villain characters. The data were analyzed using Conceptual Metaphor Theory and Blending Theory. The findings reveal that readers conceptualize villain characters through multiple source domains, including animals, non-living objects, daydreamers, supernatural beings, and plants. Among these, structural metaphors are the most frequently employed, indicating a systematic mapping between concrete source domains and abstract character traits. The analysis further demonstrates that these metaphorical constructions are influenced by factors such as physical appearance, behavioral patterns, narrative roles, and personality traits of the characters. Through blending processes, readers integrate these features to construct coherent mental representations of villains. This study contributes to cognitive linguistics by extending the application of metaphor and blending theories to user-generated discourse in digital reading environments. It highlights how readers actively participate in meaning-making by creatively conceptualizing fictional characters through everyday experiences and culturally grounded knowledge.